2007
DOI: 10.1634/stemcells.2007-0388
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hepatocyte Growth Factor Production Impairs the Ability of Adipose-Derived Stem Cells to Promote Ischemic Tissue Revascularization

Abstract: The use of adipose-derived stem/stromal cells (ASCs) for promoting repair of tissues is a promising potential therapy, but the mechanisms of their action are not fully understood. We and others previously demonstrated accelerated reperfusion and tissue salvage by ASCs in peripheral ischemia models and have shown that ASCs secrete physiologically relevant levels of hepatocyte growth factor (HGF) and vascular endothelial growth factor. The specific contribution of HGF to ASC potency was determined by silencing H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
147
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 54 publications
14
147
0
1
Order By: Relevance
“…The activity of the mTOR signaling pathway can be modulated by a variety of factors and pathways acting on different steps, and mTORC1 was activated by the binding of IGF1 to its receptor (40,43). After transplantation, ASCs remained viable at the injured site and secreted growth factors in a continuous and regulated manner in response to the environmental cues, including IGF (2,5,9,14,(22)(23)(24)37,44,46). We thus concluded that the increased muscle size, wet weight, and area of the myofibers in the ASC-transplanted groups are due to the following mechanism: The transplanted ASCs secrete growth factors; those stimulate the mTOR signaling pathway, which activates the synthesis of protein and muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the mTOR signaling pathway can be modulated by a variety of factors and pathways acting on different steps, and mTORC1 was activated by the binding of IGF1 to its receptor (40,43). After transplantation, ASCs remained viable at the injured site and secreted growth factors in a continuous and regulated manner in response to the environmental cues, including IGF (2,5,9,14,(22)(23)(24)37,44,46). We thus concluded that the increased muscle size, wet weight, and area of the myofibers in the ASC-transplanted groups are due to the following mechanism: The transplanted ASCs secrete growth factors; those stimulate the mTOR signaling pathway, which activates the synthesis of protein and muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…3E, F). ASCs remained viable after transplantation and secreted a variety of growth factors and cytokines, which activated the differentiation of satellite cells to myoblasts and from myoblasts to myotubes at the injured site (2,5,9,14,(22)(23)(24)37,44,46). The myogenic effect of these growth factors and cytokines might increase the number of myogenin-expressing myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that both BM-dMSC and ASC adherent to the AM secrete high amounts of VEGF-A, IL-8, and HGF, which are known to be important for neovascularization. 6,[41][42][43] Furthermore, adherent MSC secrete antiinflammatory cytokines such as IL-10, IL-13, and IL-1-RA that would reduce chronic inflammation observed in nonhealing wounds. 44 Interestingly, we observed that adherent BM-dMSC and ASC secrete GM-CSF which is likely to have significant patient benefit for chronic wounds when applied locally.…”
mentioning
confidence: 99%
“…The main mechanism of action for this regenerative behavior remains unclear. Cai et al (2007) suggested that this enhanced regenerative ability may be due to the secretory effects of the injected stem cells. Ong et al (2013) stated that enhanced regeneration may be due to direct engraftment and differentiation of stem cells that were introduced into the diseased joints; Pak et al (2016) postulated that it could be due the combination of secretory effects and direct engraftment of stem cells.…”
Section: Discussionmentioning
confidence: 99%